A historical narrative review through the field of tocolysis in threatened preterm birth - Tijn van Winden; Carolien Roos; Ben W. Mol; E. Pajkrt; Martijn A. Oudijk (Elsevier, 2024)
Preterm birth presents a significant challenge in clinical obstetrics, requiring effective strategies to reduce associated mortality and morbidity risks. Tocolytic drugs, aimed at inhibiting uterine contractions, are a key aspect of addressing this challenge. Despite extensive research over many years, determining the most effective tocolytic agents remains a complex task, prompting better understanding of the underlying mechanisms of spontaneous preterm birth and recording meaningful outcome measures. This paper provides a comprehensive review of various obsolete and current tocolytic drug regimens that were instituted over the past century, examining both historical contexts and contemporary challenges in their development and adoption. The examination of historical debates and advancements highlights the complexity of introducing new therapies. While the search for effective tocolytics continues, questions arise regarding their actual benefits in obstetric care and the necessity for ongoing exploration. The presence of methodological limitations in current research emphasizes the importance of well-designed randomized controlled trials with robust endpoints and extended follow-up periods.In response to these complexities, the consideration of shifting towards prevention strategies aimed at addressing the root causes of preterm labor becomes more and more evident. This potential shift may offer a more effective approach than relying solely on tocolytics to delay labor initiation.Ultimately, effectively managing threatened preterm birth necessitates ongoing investigation, innovation, and a willingness to reassess strategies in pursuit of optimal outcomes for mothers, neonates, and long-term child health.